2001
DOI: 10.1038/sj.pcan.4500541
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of treatment of BPH on sexuality

Abstract: Benign prostatic hyperplasia (BPH) can have a profound affect on a patient's quality of life and sexual function and is considered by patients to be one of the most important aspects affected by the disease. Different treatments can produce a variable response in terms of the patient's quality of life, including sexual activity and satisfaction. Varying rates of erectile dysfunction (ED) and retrograde ejaculation following surgery for BPH have been reported. In general, the incidence of these side-effects is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…However, these have been observed in therapeutic doses rarely [22,23]. The other important side effect of a blockers is impaired ejaculation or retrograde ejaculation.…”
Section: Discussionmentioning
confidence: 96%
“…However, these have been observed in therapeutic doses rarely [22,23]. The other important side effect of a blockers is impaired ejaculation or retrograde ejaculation.…”
Section: Discussionmentioning
confidence: 96%
“…73 There has been some speculation that a-blocker therapy may result in improvements in sexual function as a result of improvements in LUTS. Again, as was explained above, it is difficult to determine whether this treatment improves LUTS and subsequently ED, or whether the treatment targets both processes by targeting a shared pathophysiology.…”
Section: Luts and Ed: Effects On Clinical Managementmentioning
confidence: 99%
“…Even early studies measuring treatment outcomes after transurethral resection of the prostate reported on impotence and the obvious ejaculatory deficits after surgery 55. As electrocautery disrupts the integrity of the bladder neck and potentially scars the ejaculatory ducts, declines in ejaculatory function are extremely common with this approach (>50%),56 whereas subsequent erectile dysfunction is now rare (<5%) 57. With increasing knowledge of other potential sexual function deficits after surgical treatment, decreased libido and worsened satisfaction with sexuality 1 year after transurethral resection have also been demonstrated 58…”
Section: Introductionmentioning
confidence: 99%
“…In this literature, minimally invasive therapies seem to be less frequently associated with erectile or ejaculatory dysfunction 56,59. The effects of surgical and minimally invasive therapies vary for different aspects of male sexual function (see Table 1).…”
Section: Introductionmentioning
confidence: 99%